Chemical Amendments of Dryland Saline–Sodic Soils Did Not Enhance Productivity and Soil Health in Fields without Effective Drainage. (1st March 2019) - Birru, Girma A.; Clay, David E.; DeSutter, Thomas M.; Reese, Cheryl L.; Kennedy, Ann C.; Clay, Sharon A.; Bruggeman, Stephanie A.; Owen, Rachel K.; Malo, Douglas D.
Abstract : Core Ideas: The amount of land impacted by salinity or sodicity is increasing worldwide. Precision conservation can be used to target corrective treatments to problem areas. Chemical amendments did not enhance soil health or plant productivity in northern Great Plains soils that did not have effective drainage systems. The application of chemical amendments as preventative treatment in tile drained North America northern Great Plains fields did not improve soil health (water infiltration and microbial diversity) and either reduced or did not increase crop yields. These results were partially attributed to high subsoil bulk densities and low drainable porosities. A common restoration treatment for saline–sodic soils involves improving soil drainage, applying soil amendments (e.g., CaSO4, CaCl2, or elemental S), and leaching with water that has a relatively low electrical conductivity. However, due to high subsoil bulk densities and low drainable porosities, these treatments many not be effective in glaciated dryland systems. A 3‐yr field study conducted in three model systems determined the impact of chemical amendments (none, CaCl2, CaSO4, and elemental S) on plant growth, microbial composition, temporal changes in electrical conductivity (ECe ), and the relative sodium content (%Na). Chemical amendments (i) either reduced or did not increase maize ( Zea mays ), soybean ( Glycine max ), and sorghum ( Sorghum bicolor ) yields; (ii) did not increase water infiltration or microbial biomass as determined using the phospholipid‐derived fatty acid (PLFA) technique; and (iii) did not reduce ECe or %Na. These results were attributed to high bulk densities and low drainable porosities that reducing the drainage effectiveness in the model backslope and footslope soils, the presence of subsurface marine sediments that provided a source for sodium and other salts that could be transported through capillary action to the surface soil, high sulfate and gypsum contents in the surface soil, and relatively low microbial biomass values. The results suggests that an alternative multistep saline sodic soil restoration approach that involves increasing exchangeable Ca +2 through enhanced microbial and root respiration and increasing transpiration and soil drainage by seeding full season deep rooted perennial vegetation should be tested.